Peran Pemerintah Dalam Mendukung Kesejahteraan Masyarakat Petani Di Desa Lamoncong Kecamatan Bontocani Kabupaten Bone - Fitriani Syahrir; Usman; Syamsidar (Universitas Islam Negeri Alauddin Makassar, 2025)
This study raises the main problem of the Role of Government in Supporting the Welfare of Farming Communities in Lamoncong Village, Bontocani District, Bone Regency with the aim of knowing how the description of the welfare of farming communities in Lamoncong Village, Bontocani District, Bone Regency Based on the Perspective of Law Number 11 of 2009 concerning welfare and how government policies in improving the welfare of farmers in Lamoncong Village, Bontocani District, Bone Regency. This study uses a qualitative research type with data collection methods in the form of direct observation, interviews, documentation, then data processing techniques and data analysis are carried out by collecting data, word reduction, data presentation and drawing conclusions. The results of the study show that how the description of the welfare of farming communities based on the perspective of Law Number 11 of 2009 concerning welfare is carried out with indicators of economic welfare, social welfare indicators, indicators of welfare and education, as well as the level of social participation and how government policies in improving the welfare of farmers are carried out with access to religious education in improving welfare, access to health in improving welfare, infrastructure in improving welfare, as well as synergy of access to religious education, health and infrastructure. The implications of this study show that the active role of the government in supporting the welfare of the farming community in Lamoncong Village has a significant impact on improving the standard of living of farmers.